2021
DOI: 10.1002/adma.202008487
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Crosslinking‐Enabled Strain‐Regulating Crystallization for Stable, Efficient α‐FAPbI3‐Based Perovskite Solar Cells

Abstract: α‐Formamidinium lead triiodide (α‐FAPbI3) represents the state‐of‐the‐art for perovskite solar cells (PSCs) but experiences intrinsic thermally induced tensile strain due to a higher phase‐converting temperature, which is a critical instability factor. An in situ crosslinking‐enabled strain‐regulating crystallization (CSRC) method with trimethylolpropane triacrylate (TMTA) is introduced to precisely regulate the top section of perovskite film where the largest lattice distortion occurs. In CSRC, crosslinking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 43 publications
0
126
0
Order By: Relevance
“…Cl − has been demonstrated to improve the crystallization and reduce the non-radiative recombination of perovskites. 59,71,75–77 Methylenediammonium dichloride (MDACl 2 ), 27,28 MACl 29 and FACl 78 have already been introduced into α-FAPbI 3 . MACl is considered to be a transitional “stabilizer” that does not affect the crystal structure, and can induce the formation of α-FAPbI 3 .…”
Section: A Promising Photovoltaic Materials Of Fapbi3mentioning
confidence: 99%
See 1 more Smart Citation
“…Cl − has been demonstrated to improve the crystallization and reduce the non-radiative recombination of perovskites. 59,71,75–77 Methylenediammonium dichloride (MDACl 2 ), 27,28 MACl 29 and FACl 78 have already been introduced into α-FAPbI 3 . MACl is considered to be a transitional “stabilizer” that does not affect the crystal structure, and can induce the formation of α-FAPbI 3 .…”
Section: A Promising Photovoltaic Materials Of Fapbi3mentioning
confidence: 99%
“…This may be an effective structural stabilizer (inhibiting lattice deformation) and chemical stabilizer (enhancing the interaction between 3D grains) in FA-based perovskites. Recently, an in situ crosslinking-enabled strain-regulating crystallization (CSRC) method with trimethylolpropane triacrylate has been introduced to precisely regulate the top section of the perovskite film, where the largest lattice distortion occurs by Zhang et al 77 …”
Section: A Promising Photovoltaic Materials Of Fapbimentioning
confidence: 99%
“…For example, Zhang et al proposed a crosslinking‐enabled strain‐regulating crystallization (CSRC) method, which inserted a cross‐linking agent, trimethylolpropane triacrylate (TMTA), to precisely adjust the lattice distortion at the top of the perovskite film (FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 . [ 86 ] During the growth of perovskite, the crystal nuclei bonded with TMTA molecules were crosslinked with each other, which provided compression limit and balanced the overall thermal expansion of the crystal. Molecular crosslinking compression also “pulled” adjacent small perovskite particles together and promoted their merging into larger perovskite particles, as shown in Figure 8F.…”
Section: Improvement Of Fapbi3 Film Qualitymentioning
confidence: 99%
“…Compared with DMSO, NMP could form stronger coordination bonds to FAI in the perovskite precursor, which was beneficial to delay crystallization and generate large-grained perovskite films. 2020 [36] FTO/c-TiO 2021 [81] ITO/SnO 2021 [83] FTO/c-TiO 2 /m-TiO 2 /FAPbI [95] FTO/c-TiO 2 /m-TiO 2 / FAPbI 2017 [29] FTO/c-TiO 2019 [8] FTO/c-TiO 2 /m-TiO 2 /FAPbI 2021 [86] FTO/SnO 2021 [12] FTO/c-TiO 2 /m-TiO 2 / (FAPbI 3 ) 0.97 (MAPbBr 3 ) 0.03 /Spiro-OMeTAD/Au…”
Section: Precursor Conditionsmentioning
confidence: 99%
“…[30][31][32][33][34] COSs can be in situ crosslinked under certain conditions (such as UV light, heat, or initiators) to form an insoluble and stable polymer network, thereby freezing the perovskite morphology together with improved device stability. [35][36][37][38][39] For example, Li et al reported long-term operationable sound α-FAPbI 3 -based PerSCs through trimethylolpropane triacrylate crosslinking, which maintained 95% of initial PCE under long-term storage over 4000 h and 80% of initial PCE under light soaking for 1248 h. [40] In addition, an n-type conjugated molecule was used as an electron transport layer (ETL) on the top of perovskite to protect it from moisture and thermal, achieving considerable long-term stability. [32] While the design and application of organic molecules to realize crosslinking and coordination functions in PerSCs have been rarely studied, although it may be a facile and effective strategy to simultaneously improve the performance and stability of PerSCs.…”
Section: Introductionmentioning
confidence: 99%